2020
DOI: 10.18502/sjms.v15i4.8163
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Depression among Adult Type 2 Diabetic Patients at Al-Jemaih Diabetic Center, Dongola, Northern State, Sudan, 2019

Abstract: Background: Type 2 diabetes and depression are common diseases with bidirectional associations. Depression in diabetics leads to poor adherence to diet and medication, poor glycemic control, reduced quality of life, and increased diabetes-related healthcare expenditure. This study aimed at evaluating diabetic patients with depression to improve the quality of care delivered. Materials and Methods: An institution-based cross-sectional study was conducted among adult type 2 diabetics at Al-Jemaih Diabetic Center… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 19 publications
4
5
1
Order By: Relevance
“…The study demonstrated that 35.6% of patients with T2DM had depression. This is exactly the same to the prevalence (35.6%) of depression reported in patients with T2DM in northern Sudan [ 23 ]. The prevalence in our study was considerably lower than the prevalence of depression (44%) in patients with T2DM in Omdurman, Sudan [ 22 ].…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…The study demonstrated that 35.6% of patients with T2DM had depression. This is exactly the same to the prevalence (35.6%) of depression reported in patients with T2DM in northern Sudan [ 23 ]. The prevalence in our study was considerably lower than the prevalence of depression (44%) in patients with T2DM in Omdurman, Sudan [ 22 ].…”
Section: Discussionsupporting
confidence: 87%
“…Our study showed no significant association between gender and depression among patients with T2DM. A similar lack of association was observed among patients with T2DM in northern [ 23 ] and central Sudan [ 22 ], as well as in Malawi [ 32 ]. In contrast, gender was reported as a significant risk for depression among patients with T2DM in South Africa [ 40 ], Guinea [ 39 ], Ghana [ 19 ] and Rwanda [ 21 ].…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations